Survival for a small planet : the sustainable development agenda - Bigg, Tom (Earthscan Publications : IIED, 2004)
Experts from around the world analyse the prospects for sustainable development on all the major policy fronts following the World Summit on Sustainable Development in Johannesburg. Topics range from security to finance, from urban governance to radical partnerships, migration and health to access to resources and the role of the market. They examine the contributions that governments, business and civil society can each make to improving our prospects and set out the agenda for those working to achieve sustainability. The book comes with a free CD-ROM of Civil Society documents on the World Summit on Sustainable Development from over 500 organizations in 80 countries.